PERAN INFLUENCER DAN MEDIA SOSIAL INSTAGRAM DALAM MENINGKATKAN PROMOSI PADA SUATU BRAND - Susilawati, Agnes Dwita; Solehatun, Fifit (ANALISIS, 2023)
Marketing is one of the strategies to increase the activities of a company in terms of promoting the products it sells. In the era of the industrial revolution 4.0 now, promotional strategies must be able to take advantage of existing opportunities, must be able to use social media as marketing tools. This is because people's habits today are that they prefer to shop online. As we already know that social media is an inseparable part of today's society. By taking advantage of existing opportunities, social media can be used to promote. The current phenomenon is that the company has also collaborated with Influencers in carrying out their promotions. Influencers are usually artists or it can be from a celebrity who becomes an idol or their followers or followers from social media. Influencers themselves are partnered with a company in order to convey the purpose of the product to be promoted to certain target consumers. The research approach is a literature review approach and a qualitative descriptive method and the flow used in this study uses the AISAS (Attention, Interest, Search, Action and Share) approach.